Frequency Compensation Design of Three-Stage CMOS OTA Amplifier for RTD Applications (London Journal of Engineering Research, 2024)
In this paper, a new three-stage CMOS operational transconductance amplifier (OTA) for RTD applications is proposed. The presented structure eliminates thefeedforward path and strengthens the feedback path of compensation network together. In addition, the presented circuit uses only a small compensation capacitor on the order of 1 pF, which alleviates the chip area. The circuit is simulated using a 0.18-μm N-well CMOS technology process showing high performance and power efficiency regarding to figure of merit (FOM) factors defined in the literature. The frequency response of the proposed amplifier shows that the DC gain is about 120 dB and bandwidth is 18.8 MHz with a phase margin of 88° and power dissipation of 544 μW.
Keywords: Particleboard; urea-formaldehyde resin; curing agents; modifier-curing agent; copper composites; ionic liquid; alumina; EQCM and SEM; Machine learning; Outlier; Outlier detection; Efficiency coefficient